Damage characterization and numerical simulation of shear experiment of plain woven glass-fiber reinforced composites based on 3D geometric reconstruction. (1st February 2020) - Zeng, Qingliang; Sun, Lijuan; Ge, Jingran; Wu, Wenwang; Liang, Jun; Fang, Daining
Abstract: The investigation on the effect of defects on the mechanical properties of composites is vital to explain the failure mechanism of materials. A computer tomography (CT) scanning in-situ shear test is designed to obtain u-CT images of plain weave glass-fiber reinforced composites. The images are then applied to reconstruct the samples by using image processing techniques. Damage evolution characterization of the plain weave glass-fiber composites under in-situ shear experiment are realized by visualizing damages in three dimension. The damage evolution process is compared with the numerical simulation results to verify the materials failure mode.